Older adults with dementia: knowledge and attitudes of physicians in health units - Ana Beatriz Quintes Steiner; Alessandro Ferrari Jacinto; Vanessa de Albuquerque Citero
ABSTRACT OBJECTIVE: To describe the knowledge and attitudes of general practitioners of the basic health network of the city of São Paulo in relation to patients with dementia and identify patterns of attitudes. METHODS: A total of 10% of the basic health units in the city of São Paulo (n = 45) were randomly distributed into six regional health coordination centers. Up to two general practitioners were interviewed in each unit, with a total of 81 physicians interviewed. They answered the translated and cross-culturally adapted version for Brazil of two British questionnaires, the knowledge quiz (knowledge about dementias) and the attitude quiz (attitude towards the patient afflicted with dementia), as well as a sociodemographic and occupational questionnaire to understand the profile of general practitioners working in primary care. Descriptive data analysis, factor analysis of the main components of the attitude quiz and study of association between attitudes and knowledge were performed, in addition to the multiple linear regression test to determine the relationship between occupational profile and knowledge about attitude patterns in dementia. RESULTS: The physicians interviewed had a median of five-year graduation time; 35.8% worked exclusively with primary care, and less than 40% had completed, or were attending, medical residency or specialization. Physicians showed a lower knowledge about the diagnosis of dementia than about the epidemiology of the disease and its therapeutic management. Their attitudes towards patients afflicted with dementia resulted in four factors: proactive optimism, delegated optimism, implicit dismay, and explicit dismay. The regression study showed that the attitude of explicit dismay decreases the longer the weekly working hours of the physician in the units, and that the delegated optimistic attitude of the physician decreases in the same situation. CONCLUSION: Investment in training is essential to improve physicians' performance in the field of dementia in primary care.